Genetic determinants of HIV-1 subtype C Nef-mediated SERINC3 down-regulation - Nikeisha Samlall; Tarylee Reddy; Nasreen Ismail; Mark A. Brockman; Zabrina L. Brumme; Thumbi Ndung’u; Jaclyn K. Mann (Virology Journal)
Abstract Background Nef-mediated down-regulation of the host restriction factors SERINC3 and SERINC5 significantly enhances HIV-1 infectivity. Natural Nef polymorphisms that affect SERINC3 down-regulation are not as well-characterised as those that affect SERINC5 down-regulation, particularly in HIV-1 subtype C infection. We therefore aimed to identify genetic determinants of SERINC3 down-regulation by subtype C Nef. In addition, we investigated the role of SERINC3 down-regulation activity in disease progression and its contribution to overall Nef function, using Nef fitness model-derived E values as a proxy for overall Nef function in vivo. Methods SERINC3 down-regulation activity of 107 participant-derived Nef clones was measured using a flow cytometry-based assay in a T cell line. The relationship between SERINC3 down-regulation activity and viral load set point or rate of CD4 + T cell decline during untreated HIV infection was analysed by linear regression. Quantile regression was used to assess the contribution of SERINC3 down-regulation activity to overall Nef function. Individual Nef amino acids associated with a significantly altered SERINC3 down-regulation activity were identified using codon-by-codon Mann Whitney U tests. Results SERINC3 down-regulation activity was not a significant predictor of viral load set point nor rate of CD4 + T cell decline. SERINC3 down-regulation activity was a significant predictor of estimated Nef fitness (E values) in univariate analysis (p < 0.0001) and remained significant in multivariate analyses adjusting for other Nef functions that were measured for the same Nef clones (p < 0.02). A total of 30 amino acids were identified to be associated with differential Nef-mediated ability to down-regulate SERINC3 (p < 0.05 and q < 0.3), with 63% of these residues being in the N-terminal domain. Conclusion Although SERINC3 down-regulation did not associate significantly with markers of HIV disease progression, our results nevertheless suggest that SERINC3 down-regulation contributes significantly to overall Nef function and fitness. The identification of Nef amino acids associated with differential SERINC3 down-regulation ability may be useful for rational design of therapeutics and vaccines targeting the Nef region.